2011
DOI: 10.1194/jlr.d008888
|View full text |Cite
|
Sign up to set email alerts
|

Huh-7 or HepG2 cells: which is the better model for studying human apolipoprotein-B100 assembly and secretion?

Abstract: This article is available online at http://www.jlr.org teins (VLDL) from liver. From a clinical perspective, plasma apoB100 levels and the apoB100/apoA1 ratio are superior to any other lipoprotein-related indices used to estimate risk of acute myocardial infarction ( 1 ). This illustrates the need for a deep understanding of the cellular mechanisms that regulate apoB100 production and secretion. Although rat hepatoma McA-RH7777 cells secrete much of their apoB100 as buoyant VLDL, it would be desirable to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
101
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 21 publications
13
101
0
Order By: Relevance
“…Although there may be differences between HCVcc and patient-derived particles, e.g. in their apolipoprotein composition of viral subpopulations of different densities, as HCVcc-producing hepatocarcinoma cells are impaired at late steps of VLDL biogenesis and production (7,87,88), our study further extends these previous results (28) and underscores the notion that distinct capture molecules are used by the different HCV subpopulations to induce attachment to target cells. Although attachment of HCVcc of intermediate density, particularly, seems to be mediated by SR-BI, we found that the infectivity of low density HCVcc particles also involves a VLDL-derived component as it could be competed by VLDL and/or by purified apoE.…”
Section: Journal Of Biological Chemistrysupporting
confidence: 77%
“…Although there may be differences between HCVcc and patient-derived particles, e.g. in their apolipoprotein composition of viral subpopulations of different densities, as HCVcc-producing hepatocarcinoma cells are impaired at late steps of VLDL biogenesis and production (7,87,88), our study further extends these previous results (28) and underscores the notion that distinct capture molecules are used by the different HCV subpopulations to induce attachment to target cells. Although attachment of HCVcc of intermediate density, particularly, seems to be mediated by SR-BI, we found that the infectivity of low density HCVcc particles also involves a VLDL-derived component as it could be competed by VLDL and/or by purified apoE.…”
Section: Journal Of Biological Chemistrysupporting
confidence: 77%
“…New models such as the partially polarized and HCV-permissive HepG2 CD81/miR-122 cell line might help tackling this concern [112]. Furthermore, despite some controversy, it is generally accepted that the VLDL secretion is altered in the Huh-7 cell line [28,166]. A similar defect is observed in the HepG2 cell line, also it can be partially rescued by inhibition of MEK-ERK (mitogen-activated protein kinase kinase -extracellular signal regulated kinase) [166].…”
Section: Host Cells For the Investigation Of Hcv Entrymentioning
confidence: 99%
“…Furthermore, despite some controversy, it is generally accepted that the VLDL secretion is altered in the Huh-7 cell line [28,166]. A similar defect is observed in the HepG2 cell line, also it can be partially rescued by inhibition of MEK-ERK (mitogen-activated protein kinase kinase -extracellular signal regulated kinase) [166]. As a consequence, HCV particles produced in Huh-7-derived cell lines do not fully resemble the lipoviroparticles circulating in infected patient serum, with possible implications for entry studies.…”
Section: Host Cells For the Investigation Of Hcv Entrymentioning
confidence: 99%
“…However, most of these cell lines have impaired production of VLDL because they express pre-VLDLs that are not fully lipidated and that do not fuse with apoE-containing luminal lipid droplets (30). The resulting HCVcc particles are thus poorly associated with apoB (9), and their buoyant density profile is significantly different compared with in vivo recovered viruses (31,32).…”
mentioning
confidence: 99%